Visceral Adipose Tissue of Prediabetic and Diabetic Females Shares a Set of Similarly Upregulated microRNAs Functionally Annotated to Inflammation, Oxidative Stress and Insulin Signaling - Justyna Strycharz; Adam Wróblewski; Andrzej Zieleniak; Ewa Świderska; Tomasz Matyjas; Monika Rucińska; Lech Pomorski; Piotr Czarny; Janusz Szemraj; Józef Drzewoski; Agnieszka Śliwińska (MDPI AG, 2021)
Hypertrophic and hypoxic visceral adipose tissue (VAT) secretes proinflammatory cytokines promoting insulin resistance (IR), prediabetes and type 2 diabetes (T2DM) microRNAs (miRNAs) are markers of metabolic disorders regulating genes critical for e.g., inflammation, glucose metabolism, and antioxidant defense, with raising diagnostic value. The aim of the current study was to evaluate whether hyperglycemia is able to affect the expression of selected miRNAs in VAT of prediabetic (IFG) and diabetic (T2DM) patients vs. normoglycemic (NG) subjects using qPCR. Statistical analyses suggested that miRNAs expression could be sex-dependent. Thus, we determined 15 miRNAs as differentially expressed (DE) among NG, T2DM, IFG females (miR-10a-5p, let-7d-5p, miR-532-5p, miR-127-3p, miR-125b-5p, let-7a-5p, let-7e-5p, miR-199a-3p, miR-365a-3p, miR-99a-5p, miR-100-5p, miR-342-3p, miR-146b-5p, miR-204-5p, miR-409-3p). Majority of significantly changed miRNAs was similarly upregulated in VAT of female T2DM and IFG patients in comparison to NG subjects, positively correlated with FPG and HbA1c, yet, uncorrelated with WHR/BMI. Enrichment analyses indicated involvement of 11 top DE miRNAs in oxidative stress, inflammation and insulin signaling. Those miRNAs expression changes could be possibly associated with low-grade chronic inflammation and oxidative stress in VAT of hyperglycemic subjects.